Drifting Diaphyses: Asymmetry in Diametric Growth and Adaptation Along the Humeral and Femoral Length. Issue 10 (17th August 2015) - Maggiano, Isabel S.; Maggiano, Corey M.; Tiesler, Vera G.; Chi‐Keb, Julio R.; Stout, Sam D.
ABSTRACT This study quantifies regional histomorphological variation along the human humeral and femoral diaphysis in order to gain information on diaphyseal growth and modeling drift patterns. Three thin sections at 40, 50, and 60% bone length were prepared from a modern Mexican skeletal sample with known age and sex to give a longitudinal perspective on the drifting cortex (12 adults and juveniles total, 7 male and 5 female). Point‐count techniques were applied across eight cross‐sectional regions of interest using the starburst sampling pattern to quantify percent periosteal and endosteal primary lamellar bone at each diaphyseal level. The results of this study show a posterio‐medial drift pattern in the humerus with a posterior rotational trend along the diaphysis. In the femur, we observed a consistent lateral to anteriolateral drift and an increase in primary lamellar bone area of both, periosteal and endosteal origin, towards the distal part of the diaphysis. These observations characterize drifting diaphyses in greater detail, raising important questions about how to resolve microscopic and macroscopic cross‐sectional analysis towards a more complete understanding of bone growth and mechanical adaptation. Accounting for modeling drift has the potential to positively impact age and physical activity estimation, and explain some of the significant regional variation in bone histomorphology seen within (and between) bone cross‐sections due to differing ages of tissue formation. More study is necessary, however, to discern between possible drift scenarios and characterize populational variation. Anat Rec, 298:1689–1699, 2015. © 2015 Wiley Periodicals, Inc.